(untitled) (Journal of Face Aesthetics, 2023)
Aim. The aim of the study was to determine the relationship between missing teeth in the oral cavity and upper face wrinkles. Material and methods. The research consisted of two stages – a retrospective and a current study, in a retrospective study documentation of 100 patients was obtained, in a current study took part 50 patients. Extraoral and intraoral medical photographs of the patient`s faces were taken. Photographs from the retrospective and the current study were assessed by 3 investigators for the severity of upper facial wrinkles, based on the Skin Aging Atlas reference scale. Volume 1, Caucasian Type. Paris: EditionsMed’Com. Results. In a retrospective analysis, a result close to statistical significance with a negative Spearman’s coefficient was obtained for the relationship – reduced number of the teeth in the lateral segments and CF (wrinkles around the eyes). In a current study statistical significance was obtained for correlations: Kłp ( right side eye wrinkles), KŁl (left side eye wrinkles), UEW (left side suborbital wrinkles). Conclusions. There is a need to treat even single missing teeth in the lateral segments in order to preserve the young appearance of the face.